Towards a European recovery programme for the crisis countries - Armin Steinbach (Intereconomics, 2012)
Austerity measures alone will not suffice to generate the growth needed for recovery in Greece, Portugal, Spain and Italy. A European Recovery Programme is necessary to stimulate growth through structural reforms and fiscal stimulus. This contribution describes policy areas where non-fiscal instruments are required to boost growth and identifies fields where public and private expenditures can generate significant positive spillovers for the economy or pave the way for new growth potentials.
Keywords: 330; Austeritätspolitik; Wirtschaftsreform; Internationale Wirtschaftshilfe; Wirtschaftswachstum; Italien; Griechenland; Spanien; Portugal